DIGITAL ENTREPRENEURSHIP TRAINING FOR MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) FOR TYPICAL CULINARY OF TUBAN REGENCY - Novyandri Taufik Bahtera; Rachman Sinatriya Marjianto; Moh. Darus Salam (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: With the presence of Micro, Small and Medium Enterprises (MSMEs), it can increase economic growth, absorption of labor and reduce poverty in Indonesia, especially in Tuban Regency. MSME's in Tuban Regency continues to increase from year to year. The problems they face are in the form of narrow marketing and a lack of distribution channels for goods. In addition, MSME's players are also faced with the problem of being unable to take good photos of their products so that the product photos are not attractive to customers. MSME's players are also faced with the problem of not properly recording business financial reports because they are still mixed with personal matters. Objective: This activity aims to increase the capacity of MSME entrepreneurs through training in the fields of digital finance, digital marketing and digital photography. Methods: The method applied is in the form of interactive training, discussion, and practice, by: 1) implementing digital finance training using the BukuWarung application, 2) Participants practicing strategies in developing digital marketing by utilizing technological advances such as social media and marketplace platforms. And 3) Participants practice taking photos of their MSME's products by paying attention to the aesthetics of the right photos. Results: MSME's entrepreneurs have increased abilities and insights in applying financial bookkeeping, marketing and drawing product images by utilizing the latest technology. Conclusion: Community service partners are able to increase their business competitiveness throughinsight and expertise in financial accounting, marketing and digital photography.